ENTREPRENEURSHIP TRAINING FOR INDEPENDENT STUDENTS EXCHANGE AND STUDENTS OF FACULTY OF ECONOMICS AND BUSINESS MALIKUSSALEH UNIVERSITY - Zulfan; Sari Yulis Terfiadi (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
Entrepreneurship training has become an important aspect in enhancing entrepreneurial skills and enthusiasm among university students. For this reason, the Faculty of Economics and Business at Malikussaleh University held entrepreneurship training for students. This training presented two lecturers from the Faculty of Economics and Business of Malikussaleh University who have been successful in managing their businesses. The purpose of this training is to increase understanding of entrepreneurship, inspire and motivate students to become entrepreneurs and develop entrepreneurial skills. The number of participants who took part in this training were 108 students consisting of independent exchange students and students of the Faculty of Economics and Business at Malikussaleh University. This training provides opportunities for students to interact directly with presenters so that they can know the steps and strategies for starting and developing business ideas, as well as increasing creativity and effective marketing strategies.